Butyrate Treatment of DSS-Induced Ulcerative Colitis Affects the Hepatic Drug Metabolism in Mice - Jourova, Lenka; Satka, Stefan; Frybortova, Veronika; Zapletalova, Iveta; Anzenbacher, Pavel; Anzenbacherova, Eva; Hermanova, Petra Petr; Drabonova, Barbora; Srutkova, Dagmar; Kozakova, Hana; Hudcovic, Tomas (Frontiers in Pharmacology, 2022)
Development of inflammatory bowel disease (IBD) is associated with alterations in the gut microbiota. There is currently no universal treatment for this disease, emphasizing the importance of developing innovative therapeutic approaches. Gut microbiome derived metabolite butyrate with its well-known anti-inflammatory effect in the gut is an auspicious candidate. Due to increased intestinal permeability during IBD, butyrate may reach also liver and influence liver physiology, including hepatic drug metabolism. For this reason, the aim of this study was to clarify not only the protective effects of the sodium butyrate (SB) administration on colonic inflammation but the focus has been also on effects of SB on hepatic drug metabolism in experimental colitis induced by dextran sodium sulfate (DSS) in mice. It has been shown here that the butyrate pre-treatment can alleviate gut inflammation and reduce the leakiness of colonic epithelium by restoration of the assembly of tight junction protein Zonula occludens-1 (ZO-1) in mice with DSS-induced colitis. In this paper, butyrate along with inflammation has been shown to affect also the expression and enzyme activity of selected cytochromes P450 (CYPs) in the liver of mice. In this respect, CYP3A enzymes may be very sensitive to gut microbiome-targeted interventions as significant changes in CYP3A expression and activity in response to DSS-induce colitis and/or butyrate treatment have been also observed. With regard to medications used in IBD and microbiota-targeted therapeutic approaches, it is important to deepen our knowledge of the effect of gut inflammation and followed therapeutic interventions on the ability of the organism to metabolize drugs. This gut-liver axis, mediated through inflammation as well as microbiome-derived metabolites may affect the response to IBD therapy.